Aurintricarboxylic acid inhibits the malignant phenotypes of drug-resistant cells via translation regulation - Keke Shang; Yang Chen; Jingjie Jin; Tong Wang; Gong Zhang (Frontiers in Oncology)
Genome instability, a hallmark of cancer, leads to endless mutations that eventually cause drug resistance against almost all chemotherapy drugs. This poses a significant obstacle to the success of cancer treatments. Here, we report that aurintricarboxylic acid (ATCA) effectively suppresses the malignant phenotypes, including proliferation, migration, invasion, and clone formation, of cancer cells of multiple cancers, including cisplatin-resistant lung cancer cells, paclitaxel-resistant lung cancer cells, and doxorubicin-resistant breast cancer cells. Interestingly, ATCA does not cause acute cytotoxicity. Proteome analysis of the whole proteome and nascent chains showed that ATCA reduced translation initiation and thus reduced the abundance of the highly abundant respiratory chain complex. This lowered the potential of the mitochondrial membrane and thus restricted the energy production. This principle could be hardly circumvented by cancer cells and thus may serve as a promising and universal candidate for a second-line therapeutic agent to control cancer progression after drug resistance.